Intraspecific killing behaviour of canids: how dingoes kill dingoes. Issue 1 (2nd January 2018) - Behrendorff, Linda; Belonje, Grant; Allen, Benjamin L.
Abstract : Intraspecific conflict is an important process structuring carnivore populations. However, few data are available describing the precise mode of killing used by carnivores, especially medium-sized carnivores that can exhibit behaviours typically associated with either smaller or larger species. From records of free-ranging Australian dingoes killed during intraspecific fighting, we describe the types, location and frequency of injuries sustained, to assist in identifying killing behaviours common to medium-sized carnivores, or mesopredators. Observed injuries included superficial minor cuts and other wounds, deep punctures (bite marks or holes), severe lacerations to internal organs, tissue bruising and crushing, mutilation of muscle tissue, perforation of the chest and abdominal cavities, and a variety of bone fractures. The dingoes in this study predominately died from gross internal haemorrhaging caused by crushing bites coupled with vigorous shaking to the head, throat, neck and ventral chest areas. Our data demonstrate that dingoes used a 'bite and shake' mode of killing. This killing behaviour is dissimilar to those exhibited by large carnivores, but is consistent with behaviours shown by other medium-sized carnivores.